Associations between social support provided and walkability among older adults: Health self-consciousness as a moderator. (July 2022) - Asiamah, Nestor; Lowry, Ruth; Khan, Hafiz T.A.; Awuviry-Newton, Kofi
Highlights: This study found a positive association between neighbourhood walkability and social support provided. Health self-consciousness moderated the association between walkability and social support provided. Personal variables can affect the association between social support provided and walkability and should, therefore, be controlled for when testing this relationship. Our study suggests that improving the health literacy of seniors can maximise the positive influence of walkability on social support provided. Abstract: Background: The social support provided or given to others play a key role in healthy ageing. Empirical and anecdotal evidence suggests that walkable neighbourhoods can positively influence social support given. Higher health self-consciousness may strengthen the positive association between walkability and social support provided. Aim: This study investigated whether the association between walkability and social support provided is moderated by health self-consciousness. Methods: A cross-sectional design with sensitivity analysis and recommended procedures against common methods bias was employed. The study's population was community-dwelling older adults living in Accra, Ghana. Data from 923 participants were analysed using the hierarchical linear regression analysis. Findings: The study found a positive association between walkability and social support provided after adjusting for the ultimate confounding variables. Health self-consciousness positively moderated the association between walkability and social support provided. Conclusion: The study concludes that social support provided in older adults may be higher in more walkable neighbourhoods. Health self-consciousness can enhance the contribution of walkability to social support provided. Our results reinforce the importance of campaigns aimed at improving walkability of neighbourhoods.